Evaluation of derivative in damping in the Newtonian limit for non-planar wedge - Shetty, Shamitha; Crasta, Asha; Khan, Sher Afghan (Elsevier Ltd Kidlington Corporate Office, Kidlington, United Kingdom, 2024)
The current work derives the analytical expression for the damping derivative of a non planar wedge when c tends to one and Mach number tends to infinity. Ghosh’s developed strip theory is utilized to derive the expression of the damping derivative. Concerning various geometrical and flow characteristics, the current theory can forecast the damping derivatives of a non-planar wedge. Before performing exhaustive calculations and trial research, knowing about these damping derivatives is vital to freeze and arrive at the geometrical and kinematic similarity parameters. The ongoing technique, beneficial during the planning stage, effortlessly predicts the damping subordinates in pitch for a flat wedge. In the Newtonian limit, the equations derived for stability derivatives become precise. The pivot position is found to influence the damping derivative directly. Additionally, it has been noted that at high angles of attack, the center of pressure shifts significantly from the leading edge to the trailing edge. Consequently, according to the viewpoint of stability, this behavior may be utilized to stabilize the aeronautical vehicle. Therefore, in this case, the expression for the damping derivative is non-linear, and the findings have been affected accordingly. However, the behavior is linear up to a fifteen-degree angle of attack before the pattern becomes non-linear.